El enfoque genético y la resolución de problemas en la educación matemática aplicada a la matemática discreta (2024)
This thesis presents research focused on inquiry-based learning and the genetic approach, applied to the context of discrete mathematics, which seeks to advance the characterization of mathematical thinking. First, a review is made of the current state of the literature on the concepts of mathematical thinking, inquiry-based learning, discrete mathematics, and the genetic approach, highlighting their interrelations and the relevance of this research in the educational field, as well as its novelty and pertinence.